The safety of medications used to treat peripheral neuropathic pain, part 1 (antidepressants and antiepileptics): review of double-blind, placebo-controlled, randomized clinical trials. Issue 6 (2nd June 2020) - Selvy, Marie; Cuménal, Mélissa; Kerckhove, Nicolas; Courteix, Christine; Busserolles, Jérôme; Balayssac, David
ABSTRACT: Introduction: Peripheral neuropathic pain is a highly disabling condition for patients and a challenge for neurologists and pain physicians. Although many drugs have been assessed in scientific studies, few have demonstrated a clear clinical efficacy against neuropathic pain. Moreover, the paucity of data regarding their safety raised the question on the benefit-risk ratio when used in patients experiencing peripheral neuropathies. Areas covered: The authors conducted a review of double-blind, placebo-controlled, randomized clinical trials to assess the safety of medications used to treat neuropathic pain. This first review was focused on antidepressant and antiepileptic medications. The aim was to provide an overview of the treatment-emergent adverse events (≥10%) and the serious adverse effects described in clinical trials. Expert opinion: Among antiepileptics and antidepressants, duloxetine appeared to have the most detailed safety for the treatment of peripheral neuropathic pain. Over all studies, the most commonly reported adverse effects were dizziness, drowsiness, nausea, and constipation. Only 20.0% of the included studies (N = 90) presented a good description of adverse effects that included a statistical comparison vers us a placebo group. Important methodological improvements must be made to improve the assessment of medication safety in future clinical trials.